Autoimmune antibodies and asbestos exposure: Evidence from Wittenoom, Western Australia. Issue 7 (24th May 2018) - Reid, Alison; Franklin, Peter; de Klerk, Nick; Creaney, Jenette; Brims, Fraser; Musk, Bill; Pfau, Jean
Abstract : Background: Studies comparing different forms of asbestos are rare, and limited by the failure to compare results with unexposed populations. We compare autoimmune responses among former workers and residents of the crocidolite mining and milling town of Wittenoom, Western Australia, with an unexposed population. Methods: ANA testing using indirect immunofluorescence was performed on randomly selected serum samples from Wittenoom workers or residents and compared with those from participants of another unexposed cohort study. Results: ANA scores were higher in the Wittenoom participants compared with Busselton and the odds of being ANA positive was fivefold greater among Wittenoom participants than Busselton (OR 5.5, 95%CI 2.3‐13.0). Conclusions: This study is the first to report increased ANA positivity among persons exposed exclusively to crocidolite. This finding of a high frequency of positive ANA tests among crocidolite‐exposed subjects may be an indicator for an increased risk of systemic autoimmune diseases and needs further scrutiny.